Boosting quality education with inclusive human development: Empirical evidence from sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study examines the importance of inclusive human development in promoting education quality in a panel of forty-nine Sub-Saharan African countries for the period 2000-2012. The empirical evidence is based on Ordinary Least Squares (OLS), Fixed Effects (FE) and Quantile Regression (QR) estimations. It is apparent from the OLS and FE findings that inclusive human development has a negative effect on the outcome variable. This negative effect implies that inclusive human development improves education quality. This result should be understood in the light of the fact that the adopted education variable is a negative economic signal given that it is computed as the ratio of pupils to teachers. Therefore, a higher ratio reflects diminishing education quality. From QR, with the exception of the highest quantile, the tendency of inclusive human development in reducing poor quality education is consistent throughout the conditional distribution of poor education quality. Policy implications are discussed.
Keywords: G20; I10; I32; O40; O55; 330; Education; inclusive human development; Africa